Around the Material, Social, Technological and Political Dimensions of Particulate Pollution - Rispoli, Micol (E|C, 2023)
So-called “fine dust” – in scientific jargon Particulate Matter (PM) – is heterogeneous in chemical composition, size and origin. Its concentration is higher in areas where more or less polluting human activities take place. As is well known, particulate matter has harmful effects on human health and the health of other living beings. To monitor the level of air pollution and establish courses of action for environmental health, governments and institutions generally rely on techno-scientific approaches to collect data. While accessible to scientists and technicians, such data are too abstract for citizens to become aware of the problem and adopt more responsible behaviour. Against this backdrop, some researchers have been promoting different approaches, problematising and opening up what we usually refer to as “air pollution” and its effects on human health to speculation. By highlighting its socio-material, technological and political dimensions, these researches attempt to facilitate a better approximation to the problem – even for those without scientific expertise and knowledge – and promote the formation of a “collective subjectivity”.